Glyptothorax gopii, a new species of catfish (Teleostei: Sisoridae) from Mizoram, north-eastern India - Kosygin, Laishram; Das, Ujjal; Singh, Pratima; Chowdhury, Basudhara Roy (Zootaxa, 2019)
Glyptothorax gopii, a new sisorid catfish, is described from the Kaladan River drainage in Mizoram, northeast India. It is distinguished from its congeners in the Indian subcontinent by the combination of the following characters: an axe-shaped anterior nuchal plate element extensively in contact with the posterior nuchal plate, plicae present on the ventral surfaces of the pectoral-fin spine and outer rays of pelvic-fin rays, an elliptical thoracic adhesive apparatus, the nasal barbel not reaching the anterior margin of the eye, tuberculate skin, and two pale cream longitudinal stripes on the body. Glyptothorax alaknandi is considered a valid species.